Male infertility risk and gut microbiota: a Mendelian randomization study - Fu, Zhi-da; Wang, Yao; Yan, Hong-li (Frontiers in Microbiology, 2023)
Background: In recent decades, the decline of male sperm quality has become a worldwide phenomenon, with sperm quality of critical importance for the ability to conceive naturally. Recent studies suggest that male fertility function is closely linked to the gut microbiota, however, as yet, the cause-and-effect association between the gut microbiota and male infertility risk is unclear.Methods: We performed one two-sample mendelian randomization (MR) study, which uses summary data on human gut microbiota from the MiBioGen consortium as factors of exposure. FinnGen Consortium R8 data was used to obtain GWAS data for male infertility. To evaluate cause-and-effect associations linking gut microbiota and male infertility risk with multiple Mendelian randomization methods, which include inverse variance weighted (IVW), MR-Egger, Maximum Likelihood (ML) Ratio, etc. The heterogeneity of instrumental variables was evaluated through Cochran's Q, Rucker's Q, and leave-one-out analysis methods.We found a positive association between Allisonella, Anaerotruncus, Barnesiella, Intestinibacter, and Lactococcus and male infertility risk according to the MR analysis results. Bacteroides, Romboutsia, Ruminococcaceae (NK4A2140group), and Ruminococcaceae (UCG011) play a protective function in male infertility pathogenesis.It was found that gut microbiota and infertility are causally related in this study. In the subsequent studies, there is a need to build a larger, and more comprehensive GWAS database on male infertility, which will reveal the underlying mechanisms for gut microbiota and male infertility. There is a need for randomized controlled trials for validating the protective effect of the associated gut microbiota against male infertility risk, and for exploring the associated mechanisms.